Pengaruh Akuntabilitas Lembaga dan Transparansi Laporan Keuangan Terhadap Kepercayaan Donatur Lembaga Amil Zakat Ummur Quro (Laz- Uq) Jombang - Ziana Nurul Walidah; Lik Anah (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2020)
This study aims to determine the effect of institutional accountability and transparency of financial reports on the trust of donors at the Ummul Quro (LAZ-UQ) Jombang Amil Zakat Institution. The population in this study were all LAZ-UQ donors until 2018 totaling 4,943. Based on the research objectives that the researcher wants to achieve, namely to determine the effect of institutional accountability and transparency of financial reports on donor trust, the authors used a sample of new donors recorded as permanent donors in the last five months (the start of the March-July study) as many as 606 donors. by using the theory of Baiky (1982) in Rumidi (2006: 54) which reveals that for research using data analysis with statistics, the least number of samples is 30. The sample method used is random sampling. Analysis of the data used is multiple linear regression analysis using SPSS version 16 as the test tool.. The result of the coefficient of determination (R²) shows that the variables of institutional accountability and transparency of financial statements have an influence on donor trust by 22.1% while the remaining 77.9% (100% -22.1%) can be explained by other variables.